Application of canal automation at the Central Arizona Irrigation and Drainage District - Strand, Robert J., author; Clemmens, Albert J., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
The Central Arizona Irrigation and Drainage District (CAIDD) began delivering water to users in 1989. Although designed for automatic control, the system was run manually until a homemade SCADA (Supervisory Control and Data Acquisition) system was developed by district employees. In 2002, problems with radio communication and limitations of the homemade SCADA system prompted CAIDD to begin the process of modernization. New spread-spectrum radios and RTUs (Remote Terminal Units) were purchased along with a commercial SCADA package (iFix by GE-IP). In 2005, CAIDD decided to pursue implementation of full automated control of a majority of district check gates. Currently, 125 gates are under remote manual supervisory control and 129 water levels are remotely monitored. CAIDD chose to implement SacMan (Software for Automated Canal Management) under development by the U.S. Arid Land Agricultural Research Center, Maricopa, AZ. The decision was made to only apply full automation at gates that had gate position sensors. Thus purchase and installation of gate position sensors have slowed implementation. To date, five lateral canals have been set up for full automatic control, where SacMan routes flow changes through the canal and uses downstream water level feedback control to correct for any errors that occur. The ditchrider only makes changes at the farm turnouts and district-operated wells. Automation of the Central Main canal has been tested in simulation. Control of this canal requires special treatment, as described in a companion paper. The district is waiting until enough of the canal is ready for automation before it turns automatic controls on 24/7, since this will require some operator training and remote oversight when problems occur. We hope this occurs in the summer of 2010.
USCID water management conference
Presented at Upgrading technology and infrastructure in a finance-challenged economy: a USCID water management conference held on March 23-26, 2010 in Sacramento, California.